1999
DOI: 10.1080/026782999203832
|View full text |Cite
|
Sign up to set email alerts
|

Discotic liquid crystalline crosslinkers and anisotropic networks

Abstract: Discotic hexa-acrylates based on the triphenylene hexabenzoate group and a triacrylate based on the phenyl benzenetricarboxylate group were synthesized. The ® rst class of compounds is suitable to form anisotropic networks by photopolymerization in the nematic discotic phase. The latter compound shows only a monotropic liquid crystalline phase at low temperatures and is therefore not suitable for formation of these anisotropic networks. Phase separation was observed upon photopolymerization of homogeneous mixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
(31 reference statements)
0
12
0
Order By: Relevance
“…Chemicals. 11-Bromoundecyl methacrylate 30 and 11-(4hydroxyphenoxy)undecyl acrylate 31 were kindly provided by Philips Research. 4,4′-Biphenol, sodium iodide, anhydrous N,N-dimethylformamide, anhydrous chloroform, thionyl chloride, anhydrous tetrahydrofuran (THF), t-butyl-hydroquinone, 4-carboxybenzo-15-crown-5, terephthaloyl chloride, magnesium sulfate, hydrochloric acid (37%), and silica were purchased from Merck Life Science.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemicals. 11-Bromoundecyl methacrylate 30 and 11-(4hydroxyphenoxy)undecyl acrylate 31 were kindly provided by Philips Research. 4,4′-Biphenol, sodium iodide, anhydrous N,N-dimethylformamide, anhydrous chloroform, thionyl chloride, anhydrous tetrahydrofuran (THF), t-butyl-hydroquinone, 4-carboxybenzo-15-crown-5, terephthaloyl chloride, magnesium sulfate, hydrochloric acid (37%), and silica were purchased from Merck Life Science.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent cross-linking fixates the nanostructures. LC polymer membranes have already been investigated for water filtration. However, these materials are rarely used for gas separations. Bara et al showed the importance of molecular order for gas separation, by testing the performance of light gasses, of cross-linked LC polymer membranes with an ordered but not aligned columnar morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the eigen‐birefringence value is almost the same as the value before polymerization. And because the magnetic field orientation condition for THOcB (triphenylene hexa–octyloxybenzoate) by Ikeda et al is considered the state of ideal orientation order before polymerization, that the values are almost 0.08 suggests that the disorder of the liquid crystal orientation condition by polymerization of acrylate group virtually does not exist 26–30…”
Section: Hybrid Orientation Of Discotic Liquid Crystal12mentioning
confidence: 99%
“…14−16 However, the reactive building blocks have been limited solely to the calamitic RMs up to now and the construction mechanisms of hierarchical superstructures in the anisotropic LC solvents have not been fully understood. 17,18 Even though the developments of LCD technology have been mainly based on the calamitic molecules, the disk-shaped molecules recently start to open new doors in electrical and optical applications, 19−22 partially due to the extraordinary properties of disk-shaped molecules such as 1D electrical, thermal and photoconductivity including ferroelectric and photoelectric properties. 23−29 In this circumstance, here is a question: what is the self-assembly process for the construction of hierarchical superstructures when the building block is the disk-shaped LC with reactive functions?…”
Section: ■ Introductionmentioning
confidence: 99%